2011
DOI: 10.1016/s0140-6736(11)60438-8
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, diagnostic accuracy, and effectiveness of decentralised use of the Xpert MTB/RIF test for diagnosis of tuberculosis and multidrug resistance: a multicentre implementation study

Abstract: SummaryBackgroundThe Xpert MTB/RIF test (Cepheid, Sunnyvale, CA, USA) can detect tuberculosis and its multidrug-resistant form with very high sensitivity and specificity in controlled studies, but no performance data exist from district and subdistrict health facilities in tuberculosis-endemic countries. We aimed to assess operational feasibility, accuracy, and effectiveness of implementation in such settings.MethodsWe assessed adults (≥18 years) with suspected tuberculosis or multidrug-resistant tuberculosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
852
8
25

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 913 publications
(941 citation statements)
references
References 22 publications
42
852
8
25
Order By: Relevance
“…Unfortunately, most diagnostic tests are evaluated primarily in well-funded trials and demonstration studies, without good evidence of how they perform in the real world. For example, Xpert MTB/RIF was recommended on the basis of high-quality data about its accuracy and cost-effectiveness under controlled conditions and in a large field trial 26 ; however, emerging evidence has suggested that, in many settings, the characteristics of Xpert may be different when implemented in the field -including its sensitivity 69 , calibration 70 , positive predictive value (owing to low pre-test probability) 71 , and accuracy for rifampin resistance 72 . To make accurate assessments of the incremental value of diagnostics, we should collect such data early after launch, and update expectations and recommendations as those data become available.…”
Section: S65mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, most diagnostic tests are evaluated primarily in well-funded trials and demonstration studies, without good evidence of how they perform in the real world. For example, Xpert MTB/RIF was recommended on the basis of high-quality data about its accuracy and cost-effectiveness under controlled conditions and in a large field trial 26 ; however, emerging evidence has suggested that, in many settings, the characteristics of Xpert may be different when implemented in the field -including its sensitivity 69 , calibration 70 , positive predictive value (owing to low pre-test probability) 71 , and accuracy for rifampin resistance 72 . To make accurate assessments of the incremental value of diagnostics, we should collect such data early after launch, and update expectations and recommendations as those data become available.…”
Section: S65mentioning
confidence: 99%
“…If, for example, people with TB contact the health system on average every 6 months with a 50% chance of being diagnosed at each visit, the mean duration of infectiousness will be 1 year (approximately the prevalence/incidence ratio estimated by the World Health Organization 1 ). If a more sensitive test (for example, replacing sputum smear microscopy with Xpert MTB/RIF 26,27 ) can increase that probability of diagnosis from 0.5 to 0.75, the mean duration of disease, and thus the transmission per active case, could be cut by one-third. As a result, the projected epidemiological impact of a more sensitive diagnostic test in this framework is tremendous.…”
mentioning
confidence: 99%
“…Smear microscopy, HIV-negative 0.654 [5,8,13] Smear microscopy, HIV-positive 0.404 [5,8,13] Xpert MTB/RIF, smear-positive TB cases 0.983 [5,8] Xpert MTB/RIF, smear-negative, HIV-negative cases 0.793 [5,8] Xpert MTB/RIF, smear-negative, HIV-positive cases 0.718 [5,8] Xpert MTB/RIF rifampin testing 0.983 [5,8] Clinical diagnosis of TB 0.444 [5,8] Specificity Smear microscopy 0.982 [5,8,13] Xpert MTB/RIF 0.990 [5,8] Xpert MTB/RIF rifampin testing 0.983 [5,8] Clinical diagnosis of TB 0.869 [5,8] Return for results, probability (range)…”
Section: Sensitivitymentioning
confidence: 99%
“…The feasibility and cost-effectiveness of the Xpert have been well studied and support the implementation of the device in resource-limited settings [4][5][6][7][8]. When allocating new diagnostics, it has been recommended that public health decision-makers utilize not only data from such technical studies and registration trials, but also examine the existing epidemiology, health care infrastructure and clinical practice to optimize implementation and scale up [9].…”
Section: Introductionmentioning
confidence: 99%
“…However for pulmonary TB, Xpert has not been shown to decrease mortality 1618 . Yet, lessening diagnostic delay in persons with TBM may be more likely to lead to improved outcomes as compared to pulmonary TB given the high early mortality of TBM 19 .…”
Section: Introductionmentioning
confidence: 99%